2005
DOI: 10.1074/jbc.m504407200
|View full text |Cite
|
Sign up to set email alerts
|

The Ras/Raf-1/MEK1/ERK Signaling Pathway Coupled to Integrin Expression Mediates Cholinergic Regulation of Keratinocyte Directional Migration

Abstract: The physiologic mechanisms that determine directionality of lateral migration are a subject of intense research. Galvanotropism in a direct current (DC) electric field represents a natural model of cell re-orientation toward the direction of future migration. Keratinocyte migration is regulated through both the nicotinic and muscarinic classes of acetylcholine (ACh) receptors. We sought to identify the signaling pathway mediating the cholinergic regulation of chemotaxis and galvanotropism. The pharmacologic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 61 publications
(49 reference statements)
4
57
0
2
Order By: Relevance
“…59 MEK1/ERK signaling also increases expression of a2 and a3 integrins which promote keratinocyte migration. 60 AKT signaling increases integrin a4 expression in other cell types, 61 while PI3K signaling results in displacement of a6b4 from hemidesmosomes. This facilitates migration by loosening adhesion to basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…59 MEK1/ERK signaling also increases expression of a2 and a3 integrins which promote keratinocyte migration. 60 AKT signaling increases integrin a4 expression in other cell types, 61 while PI3K signaling results in displacement of a6b4 from hemidesmosomes. This facilitates migration by loosening adhesion to basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…siRNA Transfection Experiments-For transfection with siRNAs, we followed the standard protocol described in detail elsewhere (17). Briefly, KCs were seeded at a density of 2.5 ϫ 10 5 cells per well of a 6-well plate, and incubated for 16 -24 h to achieve ϳ70% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…The α7 subunit is first expressed on the cell surfaces of oral keratinocytes (KCs) comprising the lower third portion of the gingival epithelium, and becomes abundant at the terminal stage of cell development in the gingival epithelium (Nguyen et al, 2000). In a recent study, we found that the α7 inhibitor α-bungarotoxin (αBtx) and transfection with the small interfering RNA against α7 (siRNA-α7) can block effects of environmental tobacco smoke (ETS) and pure nicotine on human KCs (Arredondo et al, 2006b;Chernyavsky et al, 2005). The signaling through the Ras/Raf-1/MEK1/ERK steps mediated, in the most part, the α7-dependent effects.…”
Section: Introductionmentioning
confidence: 99%